Test-retest variability of multifocal electroretinography in normal volunteers and short-term variability in hydroxychloroquine users - Browning DJ; Lee C (Clinical Ophthalmology, 2014)
David J Browning,1 Chong Lee2 1Charlotte Eye, Ear, Nose and Throat Associates, 2University of North Carolina – Charlotte, Charlotte, NC, USA Purpose: To determine measurement variability of N1P1 amplitudes and the R1/R2 ratio in normal subjects and hydroxychloroquine users without retinopathy. Design: Retrospective, observational study. Subjects: Normal subjects (n=21) and 44 patients taking hydroxychloroquine (n=44) without retinopathy. Methods: Multifocal electroretinography (mfERG) was performed twice in one session in the 21 normal subjects and twice within 1 year in the hydroxychloroquine users, during which time no clinical change in macular status occurred. Main outcome measures: N1P1 amplitudes of rings R1–R5, the R1/R2 ratio, and coefficients of repeatability (COR) for these measurements. Results: Values for N1P1 amplitudes in hydroxychloroquine users were reduced compared with normal subjects by the known effect of age, but R1/R2 was not affected by age. The COR for R1–R5 ranged from 43% to 52% for normal subjects and from 43% to 59% for hydroxychloroquine users; for R1/R2 the COR was 29% in normal subjects and 45% in hydroxychloroquine users. Conclusion: mfERG measurements show high test-retest variability, limiting the ability of a single mfERG test to influence a decision to stop hydroxychloroquine; corroborative evidence with a different ancillary test is recommended in a suspicious case. Keywords: multifocal electroretinography, hydroxychloroquine, test-retest variability